2023
DOI: 10.1024/1010-0652/a000298
|View full text |Cite
|
Sign up to set email alerts
|

STUWA: Ein multifaktorielles Inventar zur Erfassung von Studienwahlmotivation

Abstract: Zusammenfassung. Forschung zu Studienwahlmotivation von Lehramtsaspirantinnen und -aspiranten hat gezeigt, dass verschiedene Motivationen die Studienwahlentscheidung beeinflussen können. Leider mangelt es an reliablen und validen Instrumenten, die verschiedene Facetten von Studienwahlmotivation studienfachübergreifend erfassen. Diese Lücke im testtheoretischen Arsenal der empirischen Bildungsforschung soll durch die Entwicklung eines multifaktoriellen Inventars zur Messung der Studienwahlmotivation (STUWA) ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
1
0
1
Order By: Relevance
“…We investigated our research questions using data from two longitudinal survey studies that had originally been conducted in consecutive student cohorts (class of 2018 and class of 2019) at a mid-sized German university. The original purpose of these studies was to validate new measurements for students’ motivation for enrollment and their interest–major fit (Janke et al, 2021). Conventional sensitivity analyses showed that analyzing effects in the subsample of 2018 with median group sizes of n = 16 (see Table 1) would have merely made it possible to detect medium to large group differences ( d = 0.63) with sufficient power of 1 – β = .80.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated our research questions using data from two longitudinal survey studies that had originally been conducted in consecutive student cohorts (class of 2018 and class of 2019) at a mid-sized German university. The original purpose of these studies was to validate new measurements for students’ motivation for enrollment and their interest–major fit (Janke et al, 2021). Conventional sensitivity analyses showed that analyzing effects in the subsample of 2018 with median group sizes of n = 16 (see Table 1) would have merely made it possible to detect medium to large group differences ( d = 0.63) with sufficient power of 1 – β = .80.…”
Section: Methodsmentioning
confidence: 99%
“…Formed by culture or personal experiences, individuals may have very different theories about the emotional consequences of specific events or actions and some of these are partly wrong, for example the assumption that money is the key to happiness (Aknin et al, 2009;Wilson & Gilbert, 2003). Affective forecasts based on those theories are also likely to be wrong to some extent (Wilson & Gilbert, 2003), for example, choosing a study major for materialistic reasons is not related to more study satisfaction (Janke et al, 2021). If one reason for prospective students' biased well-being forecasts is their use of inaccurate theories, then using a scientifically proven theory should help them make better forecasts.…”
Section: Subjective Interest-major Fit Forecast-reducing Inaccurate T...mentioning
confidence: 99%
“…Thus, the condition for an improvement is prospective students' use of inaccurate theories when making their well-being forecast. However, past research indicates that students already pay attention to their interest-major fit (an empirically proven cause of well-being, Etzel & Nagy, 2016) when choosing a study major (Janke et al, 2021;Watt et al, 2012) and thus it is likely that they also pay attention to this factor when making their well-being forecast. In addition, asking prospective students for their subjective interest-major fit forecast may have already acted as an intervention that led prospective students to take this factor into account when forecasting their well-being.…”
Section: Unexpected Findings Limitations and Future Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisherige Forschung konnte zeigen, dass ein größeres Ausmaß an intrinsischer Studienwahlmotivation (z.B. Wahl eines Studienfachs aus Interesse) mit höherer Studienmotivation, höherer Studienzufriedenheit und geringeren Studienabbruchintentionen in Verbindung steht (Janke, Messerer, Merkle & Krille, 2021;Kegel et al, 2020). Somit sollte das Interesse einen wichtigen Faktor bei der Studienwahlentscheidung darstellen, um ein erfolgreiches Studium zu ermöglichen.…”
Section: Introductionunclassified